2015
DOI: 10.3171/2015.2.spine14827
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative epidural spinal injections increase the risk of surgical wound complications but do not affect overall complication risk or patient-perceived outcomes

Abstract: OBJECT A lack of information exists on the relationship between preoperative epidural spinal injections and outcomes after spine surgery. There is concern that injections might cause local changes, increasing the infection risk and surgical difficulty. Therefore, the authors explored the relationship between preoperative spinal injections and postoperative outcome. METHODS The cohort was comprised of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…The surgical outcomes and overall complication rates were reported to be similar for both groups, except that there was a 7.4-fold higher risk of surgical site infection in patients who received injections (5.1% for patients who received epidural injections vs 0.6% for those who did not). 36 Our study also suggests higher infection rates of 3.9% (66 of 1699) in patients receiving LESI within 1 month and 2.2% (120 of 5491) in patients receiving LESI within 1-3 months of surgery. The infection rates in our study are slightly lower than those reported by Zusman et al, but our results suggest a similar trend of increased risk of infection after injections in a much larger study population.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The surgical outcomes and overall complication rates were reported to be similar for both groups, except that there was a 7.4-fold higher risk of surgical site infection in patients who received injections (5.1% for patients who received epidural injections vs 0.6% for those who did not). 36 Our study also suggests higher infection rates of 3.9% (66 of 1699) in patients receiving LESI within 1 month and 2.2% (120 of 5491) in patients receiving LESI within 1-3 months of surgery. The infection rates in our study are slightly lower than those reported by Zusman et al, but our results suggest a similar trend of increased risk of infection after injections in a much larger study population.…”
Section: Discussionsupporting
confidence: 63%
“…34 The infection rates we documented in the current study follow a similar trend, with higher rates of infection after injections performed closer to the time of surgery. Zusman et al 36 suggested the possibility of an increased risk of postoperative infection after lumbar fusion in patients who received preoperative epidural injections. Their study compared the surgical outcomes of lumbar fusion in patients with a history of epidural injections (117 patients) with those in patients who did not receive epidural injections (163 patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group also suggests the glucocorticoids prevent the natural host response to tissue injury and pathogen exposure, which leads to increased susceptibility to infection (12). It is also proposed that epidural injections can lead to epidural scarring, increased vascularization and promotion of degenerative changes at the injection site, which can potentially complicate the surgical site also (22). These multifactorial concerns all may contribute to the increased risk of surgical site infection.…”
Section: Discussionmentioning
confidence: 99%
“…Given the significant morbidity and cost associated with postoperative infection, these studies have strongly recommended against the administration of CSIs within 3 months of operative treatment. [28][29][30][31][32] However, many of these studies are case reports or case series that fail to reach the adequate number of patients necessary to draw definitive conclusions, which is a source of controversy.…”
Section: Introductionmentioning
confidence: 99%